2012
DOI: 10.1134/s1063778812040126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics of Δ0(1232) produced in p 12C and d 12C collisions at 4.2 A GeV/c

Abstract: Reconstructed momentum, transverse momentum, kinetic energy, rapidity, and emission angle distributions along with their mean values were compared for Δ 0 (1232) resonances produced in p 12 C and d 12 C collisions at 4.2 A GeV/c. Mean momentum, transverse momentum, and rapidity of protons and negative pions coming from Δ 0 (1232) decay were extracted and compared with the corresponding mean values for protons and π − mesons in experiment and the relevant model calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was shown in Refs. [1][2][3][4][5][6][7][8][9] that a significant fraction of the pions produced in relativistic hadronnucleus and nucleus-nucleus collisions in bubble chamber experiments of the Joint Institute for Nuclear Research (JINR, Dubna, Russia) originated from decay of resonances. The dominant role of resonances in pion production at the energies of the order of a few GeV/nucleon or less was also revealed in earlier papers [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in Refs. [1][2][3][4][5][6][7][8][9] that a significant fraction of the pions produced in relativistic hadronnucleus and nucleus-nucleus collisions in bubble chamber experiments of the Joint Institute for Nuclear Research (JINR, Dubna, Russia) originated from decay of resonances. The dominant role of resonances in pion production at the energies of the order of a few GeV/nucleon or less was also revealed in earlier papers [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The decay kinematics of resonances was shown to be responsible for low transverse momentum enhancement of pion spectra in hadron-nucleus and nucleus-nucleus collisions at incident beam energies from 1 to 15 GeV per nucleon [9,13,14]. It was observed that the pions that come from decay mainly populated the low transverse momentum part of the spectrum [9,13,14].…”
Section: Introductionmentioning
confidence: 99%